Cardiopulmonary Support During Catheter Ablation of Ventricular Arrhythmias With Hemodynamic Instability: The Role of Inducibility - Grimaldi, Massimo; Marino, Maria Monica; Vitulano, Nicola; Quadrini, Federico; Troisi, Federica; Caporusso, Nicola; Perniciaro, Vera; Caruso, Rosa; Duni, Nicola; Cecere, Giacomo; Martinelli, Alberto; Guida, Pietro; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background. Catheter ablation is a treatment option for sustained ventricular tachycardias (VT) that are refractory to pharmacological treatment; however, patients with fast VT and electrical storm (ES) are at risk for cardiogenic shock. We report our experience using cardiopulmonary support with extracorporeal membrane oxygenation (ECMO) during catheter ablation of VT. Methods: Sixty-two patients (mean age 68±9 years; 94% male) were referred to our center for catheter ablation of repeated episodes of hemodynamically unstable ventricular arrhythmias. ES was defined as the occurrence of ≥ 3 VT/VF episodes requiring electrical cardioversion or defibrillation in a 24-hour period. All patients had hemodynamically unstable VTs. Results. Thirty-one patients (group 1) performed catheter ablation without ECMO support and 31 patients (group 2) with ECMO support. At the end of procedure, ventricular inducibility was not performed in 16 patients of group 1 (52%) due to significant hemodynamic instability. Ventricular inducibility was performed in the other 15 patients (48%); polymorphic VTs were inducible in 8 patients. In group 2, VTs were not inducible in 29 patients (93%); polymorphic VTs were inducible in 2 patients. The median follow-up duration was 24 months. Four patients of group 1 (13%) and 5 patients of group 2 (16%) died due to refractory heart failure. An ICD intervention (shock or ATP) was documented in 13 patients of group 1 (42%) and 6 patients of group 2 (19%). Conclusions: ECMO support during catheter ablation for hemodynamically unstable VTs is a useful tool to prevent acute procedural heart failure and to reduce arrhythmic burden.